A thermodynamically consistent chemo-mechanically coupled large deformation model for polymer oxidation. (April 2020) - Konica, Shabnam; Sain, Trisha
Abstract: In this paper, a thermodynamically consistent continuum level model is developed for high temperature oxidation in polymers, that incorporates the coupling between diffusion, chemical reaction and large deformation of polymers. The kinetics of the oxidative reactions have been incorporated in the continuum model in a consistent way. The specific constitutive forms for all the physical-chemical processes are derived based on the thermodynamic inequality conditions. Deformation due to the oxidative shrinkage has been incorporated in the kinematics as an irreversible effect. Subsequently, the model is implemented in a finite element framework to analyze numerically the coupled diffusion-reaction and mechanical behavior of polymers undergoing oxidation. Several numerical simulations are performed to understand the effect of various ambient conditions and the general stress-coupled effect on the oxidative response. The model is shown to be capable of predicting the heterogeneous oxidation profile for the diffusion-limited, reaction-limited cases within a polymer material. The model has been used to track the growth of oxide layer in the case of a long-term thermo-oxidative aging process.